CENTRAL NERVOUS SYSTEM INVOLVEMENT IN ADULT ACUTE LYMPHOBLASTIC LEUKEMIA: DIAGNOSTIC TOOLS, PROPHYLAXIS AND THERAPY - Maria Ilaria Del Principe; Luca Maurillo; Francesco Buccisano; Giuseppe Sconocchia; Mariagiovanna Cefalo; Giovanna De Santis; Ambra Di Veroli; Concetta Ditto; Daniela Nasso; Massimiliano Postorino; Marco Refrigeri; Cristina Attrotto; et al. (Mediterranean Journal of Hematology and Infectious Diseases)
In adult patients with acute lymphoblastic leukemia (ALL), Central Nervous System (CNS) involvement is associated with a very poor prognosis. The diagnostic assessment of this condition relies on the use of neuroradiology, conventional cytology (CC) and flow cytometry (FCM). Among these approaches, which is the gold standard it is still a matter of debate. Neuroradiology and CC have a limited sensitivity with a higher rate of false negative results. FCM demonstrated a superior sensitivity over CC, particularly when low levels of CNS infiltrating cells are present. Although prospective studies of large series of patients are still awaited, a positive finding by FCM appears to anticipate an adverse outcome even if CC shows no infiltration. Current strategies for adult ALL CNS-directed prophylaxis or therapy involve systemic and intrathecal chemotherapy and radiation therapy. Actually, early and frequent intrathecal injection of cytostatic combined with systemic chemotherapy is the most effective strategy to reduce the frequency of CNS involvement. In patients with CNS overt ALL, at diagnosis or upon relapse, allogenic hematopoietic stem cell transplantation might be considered. This review will discuss risk factors, diagnostic techniques for identification of CNS infiltration and modalities of prophylaxis and therapy to manage it.